1997
DOI: 10.1088/0953-8984/9/15/009
|View full text |Cite
|
Sign up to set email alerts
|

Collective cyclotron modes in high-mobility two-dimensional hole systems in GaAs - (Ga, Al)As heterojunctions: I. Experiments at low magnetic fields and theory

Abstract: The cyclotron resonance of very high-mobility two-dimensional holes in GaAs - (Ga, Al)As heterojunctions grown on (111), (311) and (100) substrates has been studied over the frequency range 30 to 200 GHz. Although the presence of two hole spin subbands in the samples suggests that two cyclotron resonances should be observed, in practice only a single resonance occurs for a wide range of conditions (temperature, field) and sample properties (hole density, mobility). Furthermore, the cyclotron resonance spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
(33 reference statements)
3
30
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14] At first, 2DHSs in Si-metal-oxidesemiconductor ͑MOS͒ structures were investigated. 5 The first CR experiments on GaAs-based 2DHS were performed on Be-doped ͑100͒ samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14] At first, 2DHSs in Si-metal-oxidesemiconductor ͑MOS͒ structures were investigated. 5 The first CR experiments on GaAs-based 2DHS were performed on Be-doped ͑100͒ samples.…”
Section: Introductionmentioning
confidence: 99%
“…Other publications dealt with the influence of carrier-carrier interactions on the spin-split CRs. 13 Here, a two-level system was assumed at sufficient low B; thus, that the nonparabolicity did not play an essential role.…”
Section: Introductionmentioning
confidence: 99%
“…Within the approximation of frequency independent electron-electron scattering time, the relaxation of the relative total momentum P is governed by dP͞dt M e ͑v͒P ͑iv e 2 1͞t e ͒P. This model has been well studied, where v e shifts the CR frequencies, while t e broadens the CR peaks [19][20][21]. Such a study indicated that we are in the weak electron-electron coupling regime with almost no mixing of the two modes.…”
mentioning
confidence: 99%
“…It is clear that there are two CR peaks in general, and the size of the splitting is determined by the memory function. The electron-electron interaction can couple these two CR transitions [6,7,[19][20][21] producing a single mode or two mixed modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation